Minimally invasive percutaneous robotic thoracolumbar pedicle screw implantation combined with three‐dimensional fluoroscopy can reduce radiation: A cadaver and phantom study. Issue 5 (10th July 2019) - Spyrantis, Andrea; Cattani, Adriano; Seifert, Volker; Freiman, Thomas M.; Setzer, Matthias
Abstract: Objective: Feasibility of robotic minimal invasive pedicle screw (PS) placement in the thoracolumbar spine using preoperative three‐dimensional (3D) fluoroscopy without computed tomography (CT). Methods: In three cadavers, 12 pedicle screws were implanted in thoracolumbar segments with the robotic surgery assistant. 3D fluoroscopy was performed for preoperative referencing, planning, and identification of postoperative screw position. The radiation exposure of fluoroscopy and a CT scanner was compared, measuring the CT dose index (CTDIw ). Results: Pedicle screw positioning was graded according to the classification of Gertzbein and Robbins: 11 of 12 pedicle screws showed optimal transpedicular position (grade 1) and one was positioned less than 2 mm outside (grade 2). No major deviations were observed. Referencing with 3D fluoroscopy resulted in a CTDIw reduction of 84% in the cervical and 33% in the lumbar spine. Conclusions: Robot‐guided PS placement, using 3D fluoroscopy for referencing, is a reliable tool for minimally invasive PS implantation; radiation exposure can be reduced.